Introduction to the Theme Issue: Christian Higher Education as Character Formation - Floyd, Shawn (Christian scholar's review, 2010)
Many of our students are required to read Plato’s Gorgias at some point in their college careers. Occasionally, and after some reflection and discussion of the text, those students come to appreciate just how high the stakes are for those confronted with the Gorgias’s central question: how should one live?